LMO2-negative Expression Predicts the Presence of MYC Translocations in Aggressive B-Cell Lymphomas. (July 2017) - Colomo, Luis; Vazquez, Ivonne; Papaleo, Natalia; Espinet, Blanca; Ferrer, Anna; Franco, Catalina; Comerma, Laura; Hernandez, Silvia; Calvo, Xavier; Salar, Antonio; Climent, Fina; Mate, José Luis; et al.
Abstract : MYC translocation is a defining feature of Burkitt lymphoma (BL), and the new category of high-grade B-cell lymphomas with MYC and BCL2 and/or BCL6 translocations, and occurs in 6% to 15% of diffuse large B-cell lymphomas (DLBCLs). The low incidence of MYC translocations in DLBCL makes the genetic study of all these lymphomas cumbersome. Strategies based on an initial immunophenotypic screening to select cases with a high probability of carrying the translocation may be useful. LMO2 is a germinal center marker expressed in most lymphomas originated in these cells. Mining gene expression profiling studies, we observed LMO2 downregulation in BL and large B-cell lymphoma (LBCL) with MYC translocations, and postulated that LMO2 protein expression could assist to identify such cases. We analyzed LMO2 protein expression in 46 BLs and 284 LBCL. LMO2 was expressed in 1/46 (2%) BL cases, 146/268 (54.5%) DLBCL cases, and 2/16 (12.5%) high-grade B-cell lymphoma cases with MYC and BCL2 and/or BCL6 translocations. All BLs carried MYC translocation ( P <0.001), whereas LMO2 was only positive in 6/42 (14%) LBCL with MYC translocation ( P <0.001). The relationship between LMO2 negativity and MYC translocation was further analyzed in different subsets of tumors according to CD10 expression and cell of origin. Lack of LMO2 expression was associated with the detection of MYC translocations with high sensitivity (87%), specificity (87%), positive predictive value and negative predictive value (74% and 94%, respectively), and accuracy (87%) in CD10 + LBCL. Comparing LMO2 and MYC protein expression, all statistic measures of performance of LMO2 surpassed MYC in CD10 + LBCL. These findings suggest that LMO2 loss may be a good predictor for the presence of MYC translocation in CD10 + LBCL. Abstract : Supplemental Digital Content is available in the text.